Postnatal Depression Risk Factors: An Overview of Reviews to Inform COVID-19 Research, Clinical, and Policy Priorities - Doyle, Frances Lee; Klein, Louis (Frontiers in Global Women's Health, 2020)
The disruption of normal life due to the COVID-19 pandemic is expected to exacerbate extant risk factors for mental health problems. This may be particularly true for women who give birth during the crisis, especially those at risk for postnatal depression. Maternal postnatal depression has been identified as a public health issue with profound impacts on maternal and child wellbeing. Evidence from previous crises (e.g., earthquakes, terrorist attacks) has shown that crises significantly impact maternal mental health and some perinatal health outcomes. The aims of this paper were therefore to conduct a review to identify the established risk factors for maternal postnatal depression, and generate evidence-based hypotheses about whether the COVID-19 crisis would likely increase or decrease postnatal depression rates based on the identified risk factors. Several databases were searched during May-June 2020 for review papers (i.e. systematic reviews, meta-analyses, qualitative syntheses) using the following keywords: Depression, perinatal, postnatal, postpartum, systematic, review, predictors. Risk factors were extracted in conjunction with indicators for their strength of evidence (i.e. effect sizes, qualitative coding). Risk factors were critically evaluated in relation to their susceptibility to the impacts of the COVID-19 crisis. It was hypothesised that several health policies that were necessary to reduce the spread of COVID-19 (e.g., required restrictions) may be simultaneously impacting a range of these known risk factors and placing a larger number of women at heightened risk for postnatal depression. For instance, factors at a strong risk of being exacerbated include: Perceived low social support; exposure to traumatic events during or prior to pregnancy; significant life events occurring during pregnancy; and high stress associated with care of children. Future research and policy implications are discussed, including how policy makers could attempt to ameliorate the identified risk factors for postnatal depression following the current COVID-19 pandemic.